Faktor Penyebab dan Upaya Penanggulangan Tindak Pidana Perdagangan Orang di Wilayah Hukum Kepolisian Daerah Nusa Tenggara Timur - Nadya Novia Lado; Karolus Kopong Medan; Rudepel Petrus Leo (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
This study discusses in depth the factors that cause and efforts to overcome the crime of trafficking in persons (TPPO) in the jurisdiction of the East Nusa Tenggara Police (NTT), which is known to have the highest number of trafficking cases in Indonesia. Using a juridical-empirical approach through interviews with nine resource persons consisting of law enforcement officials, women and child protection institutions, and the community, this study shows that although the substance of the law is quite adequate, its implementation is still weak and has not been able to cause a deterrent effect for perpetrators. Limited human resources, supporting facilities, and weak coordination between institutions are the main obstacles in the law enforcement process. Countermeasures are carried out through three main aspects, namely preemptive (counseling, socialization, and community economic empowerment), preventive (port supervision, formation of a monitoring team for illegal job vacancies, and cross-sector cooperation), and repressive (investigation, arrest, and legal process against perpetrators). This research also emphasizes the importance of increasing the capacity of the apparatus, synergy between agencies, and public education as sustainable steps in reducing the number of trafficking and protecting victims as a whole.